TEACHING PARENTS OF CHILDREN WITH DISABILITIES EXERCISES IN ADAPTIVE PHYSICAL CULTURE - Lnenichka, I.A.; Bakay, I.N.; Karpova, N.V.; Kartashev, V.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to experimentally substantiate the methodology for teaching parents of children with disabilities to adaptive physical education exercises. Methods and structure of the study. The scientific work was carried out on the basis of the rehabilitation center LLC Center for Rehabilitation and Adaptive Physical Education "Together with mom" (Moscow) in the period from August 2020 to February 2021. The methodology of teaching parents contained the following means and methods of APC: correctional-directed exercises (Adaptive physical culture) APC; correctional and developmental mobile game; joint gymnastics; short seminars with parents; remote feedback method between parents and APC instructor. Results and conclusions. A modified method of teaching parents, children with disabilities, exercises of adaptive physical culture, has shown its effectiveness during the rehabilitation course for children. This achievement is due to the use of combining the theoretical part with the practical, as well as the possibility of establishing high-quality feedback between the instructor and parents during training.